Incremental validity of the episode size criterion in binge‐eating definitions: An examination in women with purging syndromes. Issue 7 (3rd February 2016) - Forney, K. Jean; Bodell, Lindsay P.; Haedt‐Matt, Alissa A.; Keel, Pamela K.
ABSTRACT: Objective: Of the two primary features of binge eating, loss of control (LOC) eating is well validated while the role of eating episode size is less clear. Given the ICD‐11 proposal to eliminate episode size from the binge‐eating definition, the present study examined the incremental validity of the size criterion, controlling for LOC. Method: Interview and questionnaire data come from four studies of 243 women with bulimia nervosa ( n = 141) or purging disorder ( n = 102). Hierarchical linear regression tested if the largest reported episode size, coded in kilocalories, explained additional variance in eating disorder features, psychopathology, personality traits, and impairment, holding constant LOC eating frequency, age, and body mass index (BMI). Analyses also tested if episode size moderated the association between LOC eating and these variables. Results: Holding LOC constant, episode size explained significant variance in disinhibition, trait anxiety, and eating disorder‐related impairment. Episode size moderated the association of LOC eating with purging frequency and depressive symptoms, such that in the presence of larger eating episodes, LOC eating was more closely associated with these features. Neither episode size nor its interaction with LOC explained additional variance in BMI, hunger, restraint, shape concerns, state anxiety, negative urgency, or global functioning. Discussion: Taken together, results support the incremental validity of the size criterion, in addition to and in combination with LOC eating, for defining binge‐eating episodes in purging syndromes. Future research should examine the predictive validity of episode size in both purging and nonpurging eating disorders (e.g., binge eating disorder) to inform nosological schemes. © 2016 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:651–662)